Isokinetic knee muscle strength of soccer players according to their position - Tourny-Chollet, C.; Leroy, D.; Leger, H.; Beuret-Blanquart, F. (2000)
The aim of our study was to compare the isokinetic concentric (60\ci.s^{-1}, 120\ci.s^{-1}, 240\ci.s^{-1}) and eccentric (60\ci.s^{-1}, 120\ci.s^{-1}) strength bilaterally of the knee muscle of soccer players in relationship to their position on the playing field. The hamstrings and quadriceps strength of 21 soccer players were evaluated with a Kin-Com®(Kinetic Communicator) isokinetic dynamometer. A predominance of the strength moments on the dominant leg compared to the non-dominant leg was not demonstrated, except for the hamstrings in a concentric mode at a 240\ci.s^{-1} speed. Both the concentric and eccentric strengths of the knee flexors and extensors decreased with the increase in angular speed. The relationship between the three positions in the game (forward, midfield, and defender) and the isokinetic strengths measured at different speeds underlined specific differences between each position. These differences were observed at the level of the co-activation of the knee flexors and extensors during the movements specific to the position and between the kicking leg and the stance leg. Isokinetics and Exercise Science, Issue: Volume 8, Number 4/2000, Pages:187 - 193